0951 Insomnia, Short-sleepers And Rem-related Sleep Disordered Breathing As Risk Factors For Incident Depression In The Episono Cohort. (27th April 2018) - Hirotsu, C; Heinzer, R; Poyares, D; Haba-Rubio, J; Coelho, F M; Bittencourt, L; Tufik, S
Abstract: Introduction: Most depressed patients suffer from sleep abnormalities such as sleep disruption, shorter REM sleep latency, insomnia, and hypersomnia. However, whether the relationship between sleep and depression is bidirectional is poorly understood. This study aimed to investigate the risk factors of incident depression among sleep-related parameters and disorders in a general population sample. Methods: This is a longitudinal study of the Episono cohort, which included a population-based sample evaluated over 8 years. At baseline and follow-up, all participants underwent type 1 polysomnography and answered sleep and mood structured questionnaires. Depression was assessed according to Beck Depression Inventory (BDI). BDI scores ≥11 were considered positive for depression. Insomnia was defined as the difficulty to initiate/maintain sleep or early awakening in the last month occurring ≥3x/week (frequent) or <3x/week (occasional). Sleep quality was evaluated by Pittsburgh Sleep Quality Index (PSQI). PSQI scores ≥6 were classified as poor sleep quality. Self-reported sleep duration was stratified in short (>6h), average (6-8h) and long (>8h). Hypopneas were evaluated using the recommended 2017 American Academy of Sleep Medicine rule. Results: From 712 participants, 633 had available data for BDI, and 402 (43 ± 13 years, 50% male) were free of depression (BDI<11) at the baseline. Of these, 98 (24.4%) presented BDI≥11 at the 8-year follow-up evaluation. After adjustment for age and sex, frequent insomnia (OR=4.38, 1.89–10.18, p=0.001), poor sleep quality (OR=2.21, 1.37–3.58, p=0.001), and short sleep duration (OR=1.85, 1.02–3.36, p=0.044) were independently associated with incident depression compared to no-insomnia, good sleep quality and average sleep duration, respectively. Moreover, an increase in baseline AHI during REM sleep of 10 units was associated with an OR of 1.14 (1.03–1.26) of incident depression. Conclusion: Insomnia, short-sleep duration, poor sleep quality, and REM-related sleep-disordered breathing are independently associated with increased risk of depression over 8 years of follow-up. Support (If Any): FAPESP, CNPq and AFIP.